Enhancing H2 evolution by optimizing H adatom combination and desorption over Pd nanocatalyst. (March 2017) - Wang, Jin; Tan, Hongyi; Jiang, Dan; Zhou, Kebin
Abstract: Catalytic hydrogen evolution plays a significant role in hydrogen production and utilization. The combinative desorption of hydrogen (Tafel step, i.e., 2H * →H2 ) from metal catalysts has been extensively reported as the rate-determining step. However, a full atomic-level understanding on how the H-Metal binding strength affects on the elementary Tafel steps is still lacking. In the current study, H2 evolution over Pd catalysts was investigated by combining theoretical and experimental techniques. Density functional theory calculations revealed that H2 evolution was governed by either the combination barriers of 2H * or the desorption barriers of molecular H2 from the surface of the palladium catalyst, which was strongly dependent on the size of Pd particles: the rate-limiting step of H2 evolution for large nanoparticles (NPs) is diffusive combination of H * across the metal surface, while both 2H * combination and H2 desorption are difficult for subnanometer-sized Pd clusters. By tuning the combined effect of H adatom combination and H2 desorption, a highly performance Pd catalyst for hydrogen evolution both for temperature-programmed palladium hydride decomposition and catalytic dehydrogenation of formate was designed and synthesized. TiO2 -supported Pd NPs that were 2 nm in size exhibited excellent activity for formate dehydrogenation with an TOF value that was as high as 2184 h −1 at 298 K. Graphical abstract: Highlights: A new mechanism for H2 evolution over the palladium catalyst is revealed. Desorption of H2 and combination of 2H* should be strictly controlled for high activity. A Pd/TiO2 catalyst with the highest activity (TOF, 2184 h −1 ) was designed and synthesized.